(untitled) (Perner’s Contacts, 2019)
The Danube, the second longest European River, flows through ten European countries. After opening of the Main-Danube Canal in 1992, the Danube was linked with the waterways of Western European countries and a new waterway that is more than 3 500 kilometres long was formed and links the North and Black Sea. The importance of this waterway consist of exchange of goods among these European countries and the production of electricity by the dams that are located on this waterway. The goals of this paper are also SWOT analysis and the volumes of goods transported on the Danube for the last few years and their prediction with using the method of least squares.